Impact of blanching pretreatment on the drying rate and energy consumption during far-infrared drying of Paprika (Capsicum annuum L.). Issue 2 (28th March 2018) - Orikasa, Takahiro; Ono, Naoki; Watanabe, Takashi; Ando, Yasumasa; Shiina, Takeo; Koide, Shoji
Abstract: We incorporated a superheated steam blanching pretreatment step into a paprika drying process and compared the far-infrared (FIR) drying rates, hardness of the sample surfaces, cell membrane stabilities, and energy consumption of blanched and non-blanched paprika. The average drying rate of blanched paprika samples during FIR drying was higher than that of non-blanched samples. The hardness and cell membrane stability of dried blanched samples were lower than those of non-blanched samples. We estimated that the softening of the sample surfaces and injury to the cell membranes caused the drying rate to increase. The total energy consumption of the FIR drying of paprika was reduced by approximately 30% by introducing the blanching pretreatment. These findings contribute to the development of environmentally friendly FIR drying techniques for paprika.